The Time Lag Between Literacy Making An Impact On Mortality The Time Lag Between Literacy Making An Impact On Mortality And Fertility Indicators : Preliminary Results - Bansal A K; Bajpai R; Indrayan A (Wolters Kluwer Medknow Publications, 1993)
It is generally believed that increase in literacy is a precursor for fertility decline and for improvement in various other aspects of health. This implies that a time lag is expected between literacy showing an impact on fertility and health levels. Data on various fertility and mortality indicators for various states of India for rural, urban and combined areas for the years 1971, 1976, 1981and 1986 was studied to investigate this time lag. Value of the square of partial correlation was calculated between literacy rate and each of the mortality and literacy indicators, and the lag giving rise to maximum value was noted. The results indicate that there is a lag of five to ten years for literacy to show an impact on mortality levels, but no lag whatsoever in literacy showing impact on fertility levels. The latter is important since it forwards the hypothesis that literacy and fertility are part of the same development process, and does not support the hypothesis that literacy is a precursor to fertility decline.